Sistem Informasi Manajemen Dana Bantuan Operasional Sekolah (Bos) Pada SMK Negeri 1 Kota Jambi - Dewi, Yenni Puspa; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2021)
The application of Information Technology has now spread in almost all fields, including the use of the School Operational Fund (BOS), perhaps all activities using operational assistance funds utilize information technology. School Operational Assistance is a government program which is basically for the provision of funding for school non-personnel operating costs for education unitsThe reporting system for school operational assistance (BOS) at State Vocational High Schools in Jambi City is still processing and processing reports using the conventional method, which is limited to using the MS program. Excel so that errors often occur, such as in inputting data to meet the form, standard, format of the school operational assistance fund (BOS) report. This caused an error so that the data became inaccurate and relevant when reporting the school operational assistance (BOS) and reports had to always be revised to the Jambi City Education Office. The purposes and benefits of this study are to analyze and study the problems of the school operational assistance management information system (BOS) at the State Vocational School of Jambi City and produce a prototype using UML tools to simplify and reduce error rates in reporting and speed up the process of reporting data to the Provincial Education Office. Jambi. The design of information systems in this study uses UML (Unified Modeling Language) tools such as usecase diagrams, activity diagrams, and class diagrams. This research produces a prototype of the school operational assistance management information system (BOS) which can present a report on school operational assistance funds. This prototype needs to be developed for further research so that it can be applied in all schools effectively and efficiently.